Facilities and Infrastructure Management in Supporting the Learning Process at Islamic State Junior High School - Yuli Ayu Suwandari; Septuri Septuri; Devin Cumbuan Putri (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
This study examined the management of educational facilities and infrastructure in supporting the learning process at MTsN 1 Bandar Lampung. Facilities and infrastructure played a crucial role in ensuring the effectiveness and efficiency of teaching and learning activities, yet their impact largely depended on how well they were managed. The objective of this research was to analyze the implementation of facilities and infrastructure management functions planning, procurement, arrangement, use, and disposal in supporting the learning process. This study employed a qualitative approach with data collected through participatory observation, structured interviews, and documentation. Data were analyzed using data reduction, data display, and conclusion drawing, with triangulation techniques applied to ensure validity. The findings indicated that the management of facilities and infrastructure was implemented systematically and supported effective learning activities, as reflected in adequate classroom conditions, functional laboratories, library services, and the integration of information and communication technology in instruction. The study concluded that comprehensive and cyclical management of facilities and infrastructure significantly contributed to the quality of the learning process. Practically, the findings provided insights for school administrators to sustain and enhance facility management, while socially reinforced the importance of organized educational resource management in improving educational quality.